2010
DOI: 10.1111/j.1365-2710.2010.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer ‘survivor-care’: I. the α7 nAChR as potential target for chemotherapy-related cognitive impairment

Abstract: SUMMARY What is known and Objective Far more patients are now surviving cancer than ever before because of major advances in the diagnosis and treatment of primary and metastatic malignancy. Adjuvant chemotherapeutic drug and combination regimens have contributed to the success. However, persistent residual adverse effects involving mild impairment of cognitive impairment have been reported. Our objective is to review and to comment on the basic science and clinical evidence of potential pharmacologic targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…While much evidence indicates that key residues in the M2 domain and the intracellular loop of the channel are involved in cationic selectivity and permeation [7, 17], including the glutamate at residue 237 of the α7 nAChR that when mutated to alanine abolishes calcium permeability of this receptor [4], little is known about the influence that the ECD plays in ion permeation. Recently, the α7 nAChRs have emerged as potential targets in the treatment of many neurological disorders, such as Parkinson’s and Alzheimer’s diseases, and schizophrenia, and even for chemotherapy-induced cognitive impairments [15, 21, 31, 41]. Furthermore, it has been shown that α7 nAChRs are expressed in macrophages where they play a key role in the cholinergic anti-inflammatory pathway [45], and they have proven to be an effective target in the treatment of sepsis, myocardial ischemia, and rheumatoid arthritis [30].…”
Section: Discussionmentioning
confidence: 99%
“…While much evidence indicates that key residues in the M2 domain and the intracellular loop of the channel are involved in cationic selectivity and permeation [7, 17], including the glutamate at residue 237 of the α7 nAChR that when mutated to alanine abolishes calcium permeability of this receptor [4], little is known about the influence that the ECD plays in ion permeation. Recently, the α7 nAChRs have emerged as potential targets in the treatment of many neurological disorders, such as Parkinson’s and Alzheimer’s diseases, and schizophrenia, and even for chemotherapy-induced cognitive impairments [15, 21, 31, 41]. Furthermore, it has been shown that α7 nAChRs are expressed in macrophages where they play a key role in the cholinergic anti-inflammatory pathway [45], and they have proven to be an effective target in the treatment of sepsis, myocardial ischemia, and rheumatoid arthritis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The failure of APOE4 carriers to respond to ketosis may indicate a more insidious metabolic problem. APOE4 carriers may be overly reliant on glucose and hence, over a lifetime, cerebral neurons are deprived of the metabolic advantages conferred by ketone body metabolism and this may be crucial to etiology of AD [ 36 ]. Importantly, this type of pharmacogenomic profiling not only offers insights into the disease process, it also allows targeting of patients who are most likely to respond to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…nAChR subtypes show distinct anatomical location, unique biophysical and pharmacological properties, and additionally have been implicated in numerous disorders. Some examples are: (1) α6β2 and α4β2 has been implicated in Parkinson’s disease [ 52 ], (2) α7 has been implicated in Alzheimer’s disease [ 53 ] and schizophrenia [ 54 ] and has been identified as the target for chemotherapy-related cognitive impairment [ 55 ]; and (3) α9α10 has been identified as the target for the development of analgesics for the treatment of chronic neuropathic pain [ 56 ]. To understand the functioning of these ligand-gated ion channel subtypes in the normal and disease states requires novel inhibitors with improved ligand-gated ion channel subtype selectivity.…”
Section: Conus Peptides That Exhibit Therapeutimentioning
confidence: 99%